Serum Level of Vitamin D (25[OH]D) in Patient with Atopic Dermatitis - Meidyta Sinantryana Widyaswari; Iskandar Zulkarnain; Diah Mira Indramaya (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Atopic Dermatitis (AD) is a chronic inflammatory relapsing skin disorder along with itchy sensation. Etiopathogenesis DA remains unclear, however in common are caused by impaired epidermal barrier function of the skin and immune system that tend to ensue infection. Vitamin D is an immunomodulator and plays an important role in the pathogenesis of DA through improving the integrity of skin barrier permeability, expression of antimicrobial peptide (AMP), which inhibit infection, and reduce inflammation. Deficiency of vitamin D may increase the development risk of DA lesion. Purpose: To evaluate the serum levels of vitamin D (25[OH]D) in patients with DA. Methods: A descriptive observational cross-sectional study, in 34 DA patients at Dermatology and Venereology Outpatient Clinic of Dr. Soetomo Hospital Surabaya. Subjects were enrolled through consecutive sampling, serum vitamin D levels were measured using enzyme-linked immunosorbent assay (ELISA) method. Results: Serum levels of vitamin D (25[OH]D) in DA patients was 22.72±14.55 ng/mL. Serum levels of vitamin D based on the severity DA: mild (30.86±22.66 ng/mL); moderate (20.42±10.13 ng/mL); and severe (18.84±8.22 ng/mL). Conclusion: Deficiency of vitamin D can occur in DA patient with low level of serum vitamin D (25[OH]D), but the relationship with the severity of DA remains to be done further research. Key words: atopic dermatitis, vitamin D (25[OH]D).